A Simple DGE Model for Inflation Targeting. (IMF Working Papers; Working Paper ;, 2007)
The paper presents a DGE model designed as a core projection tool to support monetary policy in inflation-targeting (IT) emerging market economies. The paper uses a particularly simple and flexible general equilibrium model structure that can be amended to account for various phenomena that often complicate policy analysis in emerging markets, such as persistent trends in relative prices. The model's calibration is intuitive and can draw on the vast experience many countries have with calibrating small 'gap' models of monetary policy transmission. Moreover, the definition of the model's steady state in terms of nominal expenditure ratios, rather than levels of real variables, allows for the easy use of the model in a regular forecast production cycle in an IT central bank. The paper tests the model's properties on recent Turkish data, demonstrating that the main stylized features relevant for monetary policy making are well captured by the model.